Le Projet Joshua, la cartographie au service de l’évangélisation de la planète - Hervé Théry (M@ppemonde)
The Joshua Project is a research initiative designed to map the world's ethnic groups, in order to identify those with the fewest followers of Christ. It has 17,429 “People Groups”, including 7,417 “Unreached Groups” (42.6%), totaling 3.37 billion people (42.5% of the world's population) and is developing databases (freely downloadable) for use by mission agencies to accelerate the spread of the Gospel in these areas. It is paradoxical in that it puts irreproachable geomatics techniques at the service of an evangelization project whose roots are, to say the least, ancient.ethnic groups, frontier people groups, cartography, evangelization